2017
DOI: 10.1093/jhered/esx017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Phylogeography of the Leopard Cat (Prionailurus bengalensis) Inferred from Mitochondrial Genomes

Abstract: The Leopard cat Prionailurus bengalensis is a habitat generalist that is widely distributed across Southeast Asia. Based on morphological traits, this species has been subdivided into 12 subspecies. Thus far, there have been few molecular studies investigating intraspecific variation, and those had been limited in geographic scope. For this reason, we aimed to study the genetic structure and evolutionary history of this species across its very large distribution range in Asia. We employed both PCR-based (short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
1
30
0
4
Order By: Relevance
“…Southern red muntjac split around 1.1 Mya with the Indochinese mainland population. This divergence estimation is congruent with the lineages diversi cation in Amphibians [33]; Birds [34]; Mammals [32]; bats [35] and Leopard cat [36] that occurred in Indochinese and Sundaic region. Faunal diversi cation between the Indochinese and Sundaic region might be the result of uctuation in Indian summer [37], due to the rise in sea level [38,32].…”
Section: Discussionsupporting
confidence: 81%
“…Southern red muntjac split around 1.1 Mya with the Indochinese mainland population. This divergence estimation is congruent with the lineages diversi cation in Amphibians [33]; Birds [34]; Mammals [32]; bats [35] and Leopard cat [36] that occurred in Indochinese and Sundaic region. Faunal diversi cation between the Indochinese and Sundaic region might be the result of uctuation in Indian summer [37], due to the rise in sea level [38,32].…”
Section: Discussionsupporting
confidence: 81%
“…A loss of genetic diversity during the Pleistocene as suggested by recent mitogenome coalescence times has also been found for other carnivores (e.g. 151 Ka for leopard cats, 95% CI: 87–215; [ 50 ]), suggesting that this pattern may be detectable across other Asian carnivores. Considering the deeper coalescence time of all modern African mtDNA lineages (600 Ka), the African leopards are not likely to have experienced a bottleneck to the same extent as Asian leopards.…”
Section: Discussionmentioning
confidence: 58%
“…Due to this position as sister lineage to all Asian leopards, it has been suggested that the Javan leopard represents a relict population founded from a Middle Pleistocene leopard population from the South East Asian mainland, after which it became isolated on the Sundaic islands [ 19 , 22 ]. Deep divergence between mainland and Sundaic species or populations has also been found in a range of other animals including terrestrial mammals [ 48 ] such as tigers [ 49 ] and leopard cats [ 50 ], but also birds [ 51 ], bats [ 52 ], and frogs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this position as sister lineage to all Asian leopards, it has been suggested that the Javan leopard represents a relict population founded from a Middle Pleistocene leopard population from the South East Asian mainland, after which it became isolated on the Sundaic islands (Uphyrkina et al, 2001;Wilting et al, 2016). Deep divergence between mainland and Sundaic species or populations has also been found in a range of other animals including terrestrial mammals [48] such as tigers [49] and leopard cats [50]…”
Section: Java and The Asian Leopardmentioning
confidence: 99%